Alien bryozoans in the eastern Mediterranean Sea—new records from the coast of Lebanon - Harmelin, Jean-Georges (Zootaxa, 2014)
The Levant Basin (SE Mediterranean) is the most exposed to the introduction of non-indigenous species. The current assessment of exotic bryozoans present along the coast of Lebanon has been completed by the recording of fourteen cheilostome species (one cryptogenic) collected by diving in 17 localities (2–42 m). This set of exotic bryozoans comprises ten genera, including four (Akatopora Davis, 1934, Drepanophora Harmer, 1957, Mucropetraliella Stach, 1936 and Predanophora Tilbrook, 2006) not previously reported in the Mediterranean, while Celleporaria is the most successful extra-Mediterranean genus with four species in the survey collection. A new Celleporina species, C. bitari n. sp., also collected in the Red Sea, is described. Although lessepsian migration through the Suez Canal is the main pathway for exotic bryozoans in this region, the geographic origin of some species suggests that shipping through Gibraltar Strait is also responsible to a large extent.